Service-Oriented Cost Allocation for Business Intelligence and Analytics - Grytz, Raphael; Krohn-Grimberghe, Artus (International Journal of Systems and Service-Oriented Engineering)

Service-oriented Cost Allocation for Business Intelligence and Analytics: Who pays for BI&A? - Grytz, Raphael; Krohn-Grimberghe, Artus (Proceedings of the 50th Hawaii International Conference on System Sciences (2017))
Quantifying and designing the cost pool generated by Business Intelligence and Analytics (BI&A) would improve cost transparency and invoicing processes, allowing a fairer, more exact allocation of costs to service consumers. Yet there is still no method for determining BI&A costs to provide a base for allocation purposes. While literature describes several methods for BI&A cost estimation on an ROI or resource-consumption level, none of these methods considers an overall approach for BI&A. To tackle this problem, we propose a service-oriented cost allocation model which calculates BI&A applications based on defined services, enabling a cost transfer to service consumers. This new approach specifies steps towards deriving a usable pricing scheme for an entire BI&A service portfolio – both for allocation purposes as well as improving cost evaluation of BI&A projects. Moreover, it prevents BI&A departments from being considered as the sole cost driver, increasing customer understanding and cost awareness.

Business Intelligence & Analytics Kostenrechnung: Ergebnisse einer empirischen Untersuchung - Grytz, Raphael; Krohn-Grimberghe, Artus (BI-Spektrum)

The German Precariat and the Role of Fundamental Security-Is the Unconditional Basic Income a Possible Solution for the Growing Precarity in Germany? - Gilroy, Bernard Michael; Günthner, Julia

Style Analyse im Fondsmanagement: Nicht-lineare Optimierung mit Excel Solver - Gilroy, Bernard Michael; Mykhalskyy, Vladyslav; Seiler, Volker (WiSt-Wirtschaftswissenschaftliches Studium)

Die Überprüfung der Random Walk Hypothese mit Hilfe des Variance Ratio Tests - Seiler, Volker; Kröger, Sarah; Gilroy, Bernard Michael (WiSt-Wirtschaftswissenschaftliches Studium)

Efectiveness of Official Development Assistance-Further Evidence from DAC Countries - Seiler, Volker; Taach, Evgenia

Was bedeutet die Transformation der Märkte im digitalen Zeitalter? Ökonomische Grundlagen - Kundisch, Dennis; Gutt, Dominik (Digitale Ökonomie - Wie verändern sich die Märkte?)

Random-Walk-Hypothese - Gilroy, Bernard Michael; Volker, Seiler; Kröger, Sarah (wisu - das Wirtschaftsstudium)

Correlation of the Carrier Decay Time and Barrier Thickness for Asymmetric Cubic GaN/Al0.64Ga0.36N Double Quantum Wells - Wecker, Tobias; Callsen, Gordon; Hoffmann, Axel; Reuter, Dirk; As, Donat Josef (physica status solidi (b))

Linear and nonlinear behaviour of near-IR intersubband transitions of cubic GaN/AlN multi quantum well structures - Wecker, T.; Jostmeier, T.; Rieger, T.; Neumann, E.; Pawlis, A.; Betz, M.; Reuter, Dirk; As, Donat Josef (Journal of Crystal Growth)

Incorporation of germanium for n-type doping of cubic GaN - Deppe, Michael; Gerlach, Jürgen W.; Reuter, Dirk; As, Donat Josef (physica status solidi (b))

Picosecond Acoustics in Single Quantum Wells of Cubic GaN/(Al,Ga)N - Czerniuk, T.; Ehrlich, T.; Wecker, T.; As, Donat Josef; Yakovlev, D. R.; Akimov, A. V.; Bayer, M. (Physical Review Applied)

Optical Properties of Germanium Doped Cubic GaN - As, Donat Josef; Deppe, Michael; Gerlach, Jürgen; Reuter, Dirk (MRS Advances)

Selling Value in Business Markets: Individual and Organizational Factors for Turning the Idea into Action - Terho, Harri; Eggert, Andreas; Ulaga, Wolfgang; Haas, Alexander; Boehm, Eva (Industrial Marketing Management)

The customer value proposition: evolution, development, and application in marketing - Payne, Adrian; Frow, Pennie; Eggert, Andreas (Journal of the Academy of Marketing Science)

Business service outsourcing in manufacturing firms: an event study - Eggert, Andreas; Boehm, Eva; Cramer, Christina (Journal of Service Management)

Service transition: A viable option for manufacturing companies with deteriorating financial performance? - Boehm, Eva; Eggert, Andreas; Thiesbrummel, Christoph (Industrial Marketing Management)

Visual Languages for Modeling Business Models: A Critical Review and Future Research Directions - John, Thomas; Kundisch, Dennis; Szopinski, Daniel (Proceedings of the 38th International Conference on Information Systems (ICIS), Seoul, South Korea)
A multiplicity of visual languages have been proposed for representing business models. These languages are claimed to facilitate tasks such as understanding, communicating, and innovating a business model; and have been developed rather independently by scholars from accounting, computer science, information systems, and strategy. Consequently, the existing approaches greatly differ and to some extent contradict each other, for example, regarding their understanding of the business model concept, their terminology, and their visual notations – which means there is little common ground for developing a cumulative stream of research. Therefore, we provide a systematic, cross-disciplinary review of this emerging field and synthesize the pragmatic, semantic, and syntactic foundations of the proposed approaches. Further, we derive an agenda for future research and discuss the challenges that lie ahead to advance the field.

Kundenwert

Renew or cancel? Drivers of customer renewal decisions for IT-based service contracts - Wangenheim, Florian v; Wünderlich, Nancy V; Schumann, Jan H (Journal of Business Research)
Manufacturers increasingly integrate information and communication technologies into their products so that they can provide IT-based services. Organizations that formerly concentrated on transactional sales thus confront a new challenge associated with managing service usage—retention and extracting value from investments in smart technology. This study combines a marketing and an information systems perspective in a field study conducted jointly with a large European car manufacturer. Understanding the renewal decision for IT-based service contracts requires knowledge from both disciplines. The paper shows that combining behavioral predictor variables stemming from marketing research and technology-related perceptual variables stemming from technology acceptance research increases the explanatory power and prediction accuracy of forecasting models for customer renewal decisions. Specifically, the authors show that perceptions of usefulness become more important the longer customers use IT-based services and the more services they use within the service contract.

Die zwei Perspektiven des Kundenwerts: Darstellung und Versuch einer Integration - Eggert, Andreas (Kundenwert)

Die zwei Perspektiven des Kundenwerts: Darstellung und Versuch einer Integration - Eggert, Andreas (Kundenwert)

Kundenwert – eine Einführung in die theoretischen und praktischen Herausforderungen der Bewertung von Kundenbeziehungen - Helm, Sabrina; Günter, Bernd; Eggert, Andreas (Kundenwert)

Renew or cancel? Drivers of customer renewal decisions for IT-based service contracts - Wangenheim, Florian v; Wünderlich, Nancy; Schumann, Jan H (Journal of Business Research)
Manufacturers increasingly integrate information and communication technologies into their products so that they can provide IT-based services. Organizations that formerly concentrated on transactional sales thus confront a new challenge associated with managing service usage—retention and extracting value from investments in smart technology. This study combines a marketing and an information systems perspective in a field study conducted jointly with a large European car manufacturer. Understanding the renewal decision for IT-based service contracts requires knowledge from both disciplines. The paper shows that combining behavioral predictor variables stemming from marketing research and technology-related perceptual variables stemming from technology acceptance research increases the explanatory power and prediction accuracy of forecasting models for customer renewal decisions. Specifically, the authors show that perceptions of usefulness become more important the longer customers use IT-based services and the more services they use within the service contract.
Keywords: IT-based service; Smart services; Contract renewal; Retention; Customer churn; Free trial

“Service Encounter 2.0”: An investigation into the roles of technology, employees and customers - Larivière, Bart; Bowen, David; Andreassen, Tor W; Kunz, Werner; Sirianni, Nancy J; Voss, Chris; Wünderlich, Nancy; De Keyser, Arne (Journal of Business Research)
The service encounter – one of the foundational concepts in service research – is fundamentally changing due to rapid evolutions in technology. In this paper, we offer an updated perspective on what we label the “Service Encounter 2.0”. To this end, we develop a conceptual framework that captures the essence of the Service Encounter 2.0 and provides a synthesis of the changing interdependent roles of technology, employees, and customers. We find that technology either augments or substitutes service employees, and can foster network connections. In turn, employees and customers are taking on the role of enabler, innovator, coordinator and differentiator. In addition, we identify critical areas for future research on this important topic.
Keywords: Service encounter; Technology roles; Employee roles; Customer roles; Employee experience; Customer experience

A Nice and Friendly Chat With a Bot: User Perceptions of AI-Based Service Agents - Wünderlich, Nancy; Paluch, Stefanie (Proceedings of the 38th International Conference on Information Systems (ICIS 2017))

How to Design Successful Gamification in Retail: The benefits and Pitfalls of Affordances - Teßmer, Isabel; Olsson, Marcus; Gustafsson, Anders; Wünderlich, Nancy (Proceedings of the 2017 Frontiers in Service Conference)

The Role of Contract Types for Employees’ Public Service Motivation - Grund, Christian; Thommes, Kirsten (Schmalenbach Business Review)

Age diversity and its effects on team performance - Klabuhn, Janny; Thommes, Kirsten (Academy of Management Proceedings)

As Asynchronous Adaption of a Churn-resistant Overlay Network - Banh, Ngoc Chi

Routing in Hybrid Communication Networks with Holes - Considering Bounding Boxes as Hole Abstractions - Sundermeier, Jannik

Price Fluctuations in Online Leasing - Feldkord, Björn; Markarian, Christine; Meyer auf der Heide, Friedhelm (Proceedings of the 11th Annual International Conference on Combinatorial Optimization and Applications (COCOA))

A Self-Stabilizing Protocol for Graphs of Diameter Two - Knollmann, Till

Self-Stabilizing Spanners for Tree Metrics - Götte, Thorsten

Deep Learning Assisted Heuristic Tree Search for the Container Pre-marshalling Problem - Hottung, André; Tanaka, Shunji; Tierney, Kevin (CoRR abs/1709.09972)

Towards DevOps in Multi-provider Projects - Fazal-Baqaie, Masud; Güldali, Baris; Oberthür, Simon (CSE@SE 2017)

Overcoming Ehrlich-Schwöbel barrier in (1 1 1)A GaAs molecular beam epitaxy - Ritzmann, Julian; Schott, Rüdiger; Gross, Katherine; Reuter, Dirk; Ludwig, Arne; Wieck, Andreas D. (Journal of Crystal Growth)

Robust Si 3 N 4 masks for 100 nm selective area epitaxy of GaAs-based nanostructures - Zolatanosha, Viktoryia; Reuter, Dirk (Microelectronic Engineering)

Focused ion beam supported growth of monocrystalline wurtzite InAs nanowires grown by molecular beam epitaxy - Scholz, Sven; Schott, Rüdiger; Labud, Patrick A.; Somsen, Christoph; Reuter, Dirk; Ludwig, Arne; Wieck, Andreas D. (Journal of Crystal Growth)

Spin dynamics of quadrupole nuclei in InGaAs quantum dots - Kuznetsova, M. S.; Cherbunin, R. V.; Gerlovin, I. Ya.; Ignatiev, I. V.; Verbin, S. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Detection and Control of Spin-Orbit Interactions in a GaAs Hole Quantum Point Contact - Srinivasan, A.; Miserev, D. S.; Hudson, K. L.; Klochan, O.; Muraki, K.; Hirayama, Y.; Reuter, Dirk; Wieck, A. D.; Sushkov, O. P.; Hamilton, A. R. (Physical Review Letters)

Local Algorithms for the Continuous Gathering Problem - Podlipyan, Pavel

Scheduling with Scarce Resources - Riechers, Sören

Cost-efficient Scheduling on Machines from the Cloud - Mäcker, Alexander; Malatyali, Manuel; Meyer auf der Heide, Friedhelm; Riechers, Sören (Journal of Combinatorial Optimization)

Knowledge-based Verification of Service Compositions - Walther, Sven

Minimizing downtimes: Using dynamic reconfiguration and state management in SDN - Schwabe, Arne; Rojas, Elisa; Karl, Holger (2017 IEEE Conference on Network Softwarization, NetSoft 2017, Bologna, Italy, July 3-7, 2017)

Demo: OpenC2X — An open source experimental and prototyping platform supporting ETSI ITS-G5 - Laux, Sven; Pannu, Gurjashan Singh; Schneider, Stefan Balthasar; Tiemann, Jan; Klingler, Florian; Sommer, Christoph; Dressler, Falko (2016 IEEE Vehicular Networking Conference (VNC))

Predicting Rankings of Software Verification Tools - Czech, Mike; Hüllermeier, Eyke; Jakobs, Marie-Christine; Wehrheim, Heike (Proceedings of the 3rd International Workshop on Software Analytics)
Today, software verification tools have reached the maturity to be used for large scale programs. Different tools perform differently well on varying code. A software developer is hence faced with the problem of choosing a tool appropriate for her program at hand. A ranking of tools on programs could facilitate the choice. Such rankings can, however, so far only be obtained by running all considered tools on the program.In this paper, we present a machine learning approach to predicting rankings of tools on programs. The method builds upon so-called label ranking algorithms, which we complement with appropriate kernels providing a similarity measure for programs. Our kernels employ a graph representation for software source code that mixes elements of control flow and program dependence graphs with abstract syntax trees. Using data sets from the software verification competition SV-COMP, we demonstrate our rank prediction technique to generalize well and achieve a rather high predictive accuracy (rank correlation > 0.6).

SONATA: Service programming and orchestration for virtualized software networks - Dräxler, Sevil; Karl, Holger; Peuster, Manuel; Razzaghi Kouchaksaraei, Hadi; Bredel, Michael; Lessmann, Johannes; Soenen, Thomas; Tavernier, Wouter; Mendel-Brin, Sharon; Xilouris, George (2017 IEEE International Conference on Communications Workshops (ICC Workshops))
In conventional large-scale networks, creation and management of network services are costly and complex tasks that often consume a lot of resources, including time and manpower. Network softwarization and network function virtualization have been introduced to tackle these problems, aiming at decreasing costs and complexity of implementing new services, maintaining the implemented services, and managing available resources in service provisioning platforms and underlying infrastructures. To experience the full potential of these approaches, innovative development support tools and service provisioning environments are needed. To answer these needs, we introduce the architecture of the open-source SONATA system, a service programming, orchestration, and management framework. We present a development toolchain for virtualized network services, fully integrated with a service platform and orchestration system. We introduce the modular and flexible architecture of our system and discuss its main components and features, such as function- and service-specific managers that allow fine-grained service management, slicing support to facilitate multi-tenancy, recursiveness for improved scalability, and full-featured DevOps support.